Detection of V617F mutation of gene jak2 at patients with chronic myeloproliferative neoplasms - Dybkov, M.V.; Gartovska, I.R.; Maliuta, S.S.; Telegeev, G.D. (Вiopolymers and Cell, 2010)
The aim of the work was to create a protocol for detecting the V617F mutation of the gene jak2 in samples of patients with chronic myeloproliferative neoplasm which is necessary to unify the procedures of the analysis of blood samples according to WHO criteria for this group of diseases. Methods. Mutation was revealed using reverse transcriptase PCR and direct sequencing of PCR products. Results. Six samples of blood of patients with polycythemia vera were analyzed and the mutation V617F was detected in all six cases. This mutation was not detected in any of RNA samples of healthy donors. A case of simultaneous detection of mutations V617F and fused bcr/abl gene in CML patient was described. Conclusions. The proposed method for detecting the V617F mutation allows molecular genetic differential diagnosis of myeloproliferative neoplasm as well.